Powder injection molded nano copper oxide grafted graphene reinforced copper matrix composites - Naseer, A. (Elsevier B.V., 2022)
The challenges associated with inhomogeneous distribution, poor interfacial interaction, and agglomeration of graphene sheets in sintered metal composites restrict its effectiveness in improving mechanical and physical properties. This study devised a grafting protocol for attachment of metal oxides on graphene nanoplatelets (GNPs) to investigate its effect on dispersion and interaction with Cu matrix. GNPs were sonicated to enhance its functionalization without a considerable change in defect ratio followed by grafting of Cu2O nanoparticles on GNPs employing a co-precipitation protocol. XPS, Raman spectroscopy, XRD, FTIR, FESEM confirmed the successful growth of homogenously distributed Cu2O nanoparticles on GNPs. Subsequently, the interaction of Cu2O grafted GNPs with copper matrix was explored using powder injection molding (PIM). Microstructural analysis showed restricted agglomeration, improved distribution of GNPs in copper matrix, and most importantly, bridged interaction between bulk copper and graphene in sintered samples. Furthermore, the densification can still be improved by optimizing the sintering process. Â© 2022 Elsevier B.V.